Advancements in Carbohydrate Scaffold Synthesis: Exploring Prins Cyclization Methodology - Sateesh Dubbu; Santhi Jampani (Reactions)
The synthesis of natural and unconventional compounds with carbohydrate structures is of great interest to glycochemists due to their vital biological roles. In recent years, there has been significant progress in developing direct and indirect synthetic strategies for constructing sugar moieties. Among these methods, the Prins reaction, employing homoallylic alcohols and carbonyl compounds, has proven invaluable for directly creating sugar skeletons. This review discusses approaches for crafting carbohydrate frameworks using the Prins reaction, utilizing both carbohydrate and non-carbohydrate starting materials.